Microstructure, mechanical, and cutting performance properties of B4C and SiC reinforced sandwich composite segments - Islak, Serkan; Çelik, Ertuğrul; Erol, Mümtaz; Houssain, Hasaneen (Elsevier BV, 2024)
This study aims to extend the work-life of diamond-cutting segments and to economize the operating cost of diamond-cutting tools. In order to achieve this object, bronze matrix sandwich segments reinforced with SiC and B4C were produced utilizing the hot pressing technique. In the term of the cutting segments, it is favorable that the outer layers are wear-resistant and the middle layer is tough. SEM and XRD analysis were used to determine the microstructural properties. Mechanical properties were evaluated by conducting hardness, wear, cutting performance, and three-point bending tests. The cutting performance of the segments was determined by turning andesite marble. SEM examinations showed that SiC and B4C grains were homogeneously distributed in the bronze matrix. The highest hardness value was 113.9 HB in the B4C reinforced sandwich segment. The reciprocating wear test findings indicated that the matrix exhibited the lowest wear rate in the B4C reinforced sandwich composite segment, followed by the hybrid sandwich composite segment. The lowest amount of cutting loss after turning andesite stone was achieved in the SiC, and B4C reinforced hybrid sandwich composite segment. The cutting performance of the hybrid sandwich composite segment increased by 46.15% compared to the conventional segment without additives. The highest value of the transverse rupture strength of the specimens was 380 MPa for the B4C reinforced sandwich composite segment and 352 MPa for the hybrid sandwich composite segment. Considering all the tests and analyses, the hybrid sandwich composite segment sample may be the most suitable for diamond-cutting tools.